Making of wood composite by using natural rubber latex as an adhesive - Norlirabiatuladawiyah, Che Ani (2014)
A preliminary investigation into Natural Rubber Latex (NR) and starch adhesives for use in the manufacture of Medium Density Fiber (MDF) panels from rubber wood fibers is reported. This research is on increasing the mechanical strength and physical properties of MDF using Natural Rubber Latex (NR) as an adhesive. NR latex has ability to increase mechanical properties of MDF by doing a chemical formulation itself. In others word, NR latex not give a good result in mechanical testing without any others chemical improvement just like we added starch to give the better strength of MDF. Three samples which are 5g of starch with 15g of NR latex, 10g starch with 10g of NR latex and 15g of starch with 5g of NR latex were prepared. Adhesive preparation trials, physico-chemical testing of adhesives and mechanical testing of adhesives bonded to MDF have been completed. The morphology of the specimens was characterized using Thermo gravimetric Analysis (TGA) and Fourier Transform Infrared Spectroscopy (FTIR). The mechanical results of these limited tests show that when 10g starch with 10g NR latex shows more strength compared to other two variables. From the TGA graph, it was observed that the thermal stability of composite based on starch was higher than composite with less composition on starch